LunaR: Overview of a versatile Raman spectrometer for lunar exploration - Cloutis, E. A.; Caudill, C.; Lalla, E. A.; Newman, J.; Daly, M.; Lymer, E.; Freemantle, J.; Kruzelecky, R.; Applin, D.; Chen, H.; Connell, S.; Fernandes, D.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The LunaR concept study investigated the scientific value, feasibility, and deployment options for a Raman spectrometer on future lunar landed missions. It consists of a breadboard instrument that covers the 150–4000 cm−1 wavelength range with a resolution of ∼6 cm−1; Raman scattering is induced by a 532 nm continuous wave laser. The current conceptual design envisions the Raman spectrometer performing a downward-looking, 90-point one-dimensional across-track scan (±45°off nadir) of the lunar surface with the instrument mounted on the underside of a rover. A downward-looking context camera would provide information on the physical nature of targets interrogated by the Raman spectrometer and localization of the Raman spectra. Our laboratory investigations indicate that Raman spectroscopy is applicable to addressing a wide range of lunar surface exploration goals related to geology, in situ resource identification, and condensed volatile detection in diverse geological terrains, including permanently shadowed regions. Testing of a breadboard and commercial instrument on lunar samples and analogues indicates that a complete spectral scan of a target of interest can be completed in ∼90 min, permitting its use on even short-duration lunar landed missions. All of the major minerals present on the Moon can be detected, and in many cases their compositions can be quantified or constrained.